The Missing LNK: Evolution from Cytosis to Chronic Myelomonocytic Leukemia in a Patient with Multiple Sclerosis and Germline SH2B3 Mutation. (1st March 2022) - Gundabolu, Krishna; Dave, Bhavana J.; Alvares, Carmelita J.; Cannatella, Jeffrey J.; Bhatt, Vijaya R.; Maness, Lori J.; Al-Kadhimi, Zaid S.; Zabad, Rana K.; Cushman-Vokoun, Allison M.
Abstract : Chronic myelomonocytic leukemia (CMML) is a rare but distinct hematological neoplasm with overlapping features of myelodysplastic syndrome (MDS) and myeloproliferative neoplasm (MPN). Individuals with CMML have persistent monocytosis and bone marrow dyspoiesis associated with various constitutional symptoms like fevers, unintentional weight loss, or night sweats. It is established that there is a strong association of CMML with preceding or coexisting autoimmune diseases and systemic inflammatory syndromes affecting around 20% of patients. Various molecular abnormalities like TET2, SRSF2, ASXL1, and RAS are reported in the pathogenesis of CMML, but no such mutations have been described to explain the strong association of autoimmune diseases and severe inflammatory phenotype seen in CMML. Germline mutation in SH2B adaptor protein 3 ( SH2B3 ) had been reported before to affect a family with autoimmune disorders and acute lymphoblastic leukemia. In this report, we describe the first case of a female subject with many years of preceding history of multiple sclerosis before the diagnosis of CMML. We outline the evidence supporting the pathogenic role of SH2B3 p.E395K germline mutation, connecting the dots of association between autoimmune diseases and CMML genesis.